The effects of Aquilaria malaccensis leaves aqueous extract on sperm of sprague dawley rats towards early embryogenesis. - Ismail, Faridah; Abdul Wahab, Azantee Yazmie; Md Isa, Muhammad Lokman; Muhammad, Hussin; Raja Ismail, Raja Arif Shah; Abdul Razak, Redzuan Nul Hakim (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2019)
Introduction: Oxidative stress induced by excessive and unopposed levels of reactive oxygen species in male reproductive system results in impaired sperm quality, fertilization capacity and poor embryo development. Our goal is to assess the potential effects of Aquilaria malaccensis (AM) leaves, a plant with strong antioxidant property on early embryo development in vitro and embryo quality following fertilization with cyclophosphamide (CP) exposed rat sperm. Materials and Methods: Twenty four male Sprague Dawley rats were allocated into eight groups of three rats (n = 3): control, CP only (200 mg/kg), AM only (100 mg/kg, 300 mg/kg and 500 mg/kg) and CP + AM (100 mg/kg, 300 mg/kg and 500 mg/kg). Animals were sacrificed after 63 days of treatment and sperm from caudal epididymis were taken for in vitro fertilization (IVF) with oocytes from untreated female. Fertilization, embryo division and embryo morphology were examined at 8 and 48 hours post insemination and compared between groups. Statistical evaluations were performed using Chi-Square test and Fisher’s exact test and p-value<0.05 was considered significant. Results: Administration of AM leave extract at 100 mg/kg/day to normal rats and CP-exposed rats has significantly increased (p<0.05) the fertilization rate, early cleavage rate and embryo quality when compared to CP only treated group. However, other groups showed no significant differences. Conclusion: Overall, the present results indicate the potential of AM leave extract supplementation to improve the fertility and early embryo development in male rat exposed to CP by inhibiting the oxidative processes and scavenging free radicals.